Development of Teaching Materials for Negotiating Texts Based on Interactive Multimedia According to Design Experts for Students in 10th Grade Class Level of Tritech Informatika Vocational School Medan - Tri Andini; M. Oky Fardian; Wisman Hadi (Budapest International Research and Critics University, 2019)
One product of technology that can be used to develop teaching materials for the learning process is interactive multimedia which is a combination of various media in the form of text, graphics, audio, and interactions that are used to convey information messages from sender to receiver equipped with a controller which can be operated by the user. Efforts can be made to make learning effective one of which is the use of multimedia in interactive learning. Tritech Vocational School which will be the target of research is Information Technology Vocational High School. This school has implemented a learning system that utilizes technology as a medium and aids in learning activities, but not all subject teachers apply the same thing. Indonesian language learning in particular still uses teaching books as a guide and the only source of learning. This is one of the causes of learning activities in Indonesian language subjects tend to be monotonous and boring, because learning activities are still teacher-centered, so there is no interaction with students. This method of research is development research (Research and Development) which is a study used to produce certain products and test the effectiveness of these products. This research develops Indonesian language teaching materials in interactive multimedia-based negotiating text material for grade 10th in Tritech Informatika vocational Highschool, Medan, North Sumatera, Indoneisa.